2018
DOI: 10.1038/s41598-018-27497-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of individual populations within polymicrobial biofilms

Abstract: Selecting appropriate tools providing reliable quantitative measures of individual populations in biofilms is critical as we now recognize their true polymicrobial and heterogeneous nature. Here, plate count, quantitative real-time polymerase chain reaction (q-PCR) and peptide nucleic acid probe-fluorescence in situ hybridization (PNA-FISH) were employed to quantitate cystic fibrosis multispecies biofilms. Growth of Pseudomonas aeruginosa, Inquilinus limosus and Dolosigranulum pigrum was assessed in dual- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 92 publications
0
24
0
2
Order By: Relevance
“…DNA extraction is another critical step, especially in a multispecies sample, since cell lysis is not equal for all the microbial cells in the sample (Lopes et al . ).…”
Section: Root Canal Biofilm Model Systems: Factors To Considermentioning
confidence: 97%
“…DNA extraction is another critical step, especially in a multispecies sample, since cell lysis is not equal for all the microbial cells in the sample (Lopes et al . ).…”
Section: Root Canal Biofilm Model Systems: Factors To Considermentioning
confidence: 97%
“…The estimation of the relative contribution of the two partners in the makeup of a dual biofilm is very important to explain both the structural and functional properties of the system (Lopes et al, 2018). To this aim, the approach of colony counting has been used for fungal quantification in dual biofilms involving dimorphic species, such as C. glabrata and C. albicans in association with either Streptococcus mutans (Pereira-Cenci et al, 2008) or Staphylococcus aureus (Zago et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study aimed at comparing five different assay methods for the measurement of fungal growth, namely colony counting, determination of ergosterol or beta-N-acetylhexosaminidase activity, quantitative PCR and microscopic spore counting, the first method exhibited a coefficient of variation of replicated samples (CV r ) that was twice as high the other methods (Mensah-Attipoe et al, 2016). Moreover, marked discrepancies between plate count and molecular tools, relying on qPCR of 16S rRNA and peptide nucleic acid probe fluorescence in situ hybridization (PNA-FISH), were even observed in quantifying populations inhabiting dual and three-membered bacterial biofilms (Lopes et al, 2018). The same authors suggested that at least two quantification techniques might be needed to gain reliable estimates of the relative abundances of the biofilm’s contributors.…”
Section: Discussionmentioning
confidence: 99%
“…For counting of the biofilm-associated cells, the biofilm was first washed three times with 1.0% NaCl, then scraped out from the microtiter well, and resuspended into 1.0% NaCl as described by Leuck et al 25 and Lopes et al 26 The bacterial suspension was serially 10-fold diluted with 1.0% NaCl and appropriate dilutions were plated. TSA-NaCl plates were used for plating in the experiments with single culture, whereas CHROMagar for Vibrio and CHROMagar for E. coli were used in the experiments with mixed culture.…”
Section: Counting Of the Bacterial Cell Numbersmentioning
confidence: 99%